Impact of Diakonia, Koinonia and Marturia Services for the Growth of the Indonesian Christian Church Resident Sudirman Surabaya - Wimpie Tanojo (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2020)
The ministries of Diakonia, Koinonia and Marturia are the foundation of a church, meaning that a church that is aware of its duty and calling on this earth must rely on these three ministries. It can be said that the true main duty of the church is reflected in the ministry of Diakonia, Koinonia and Marturia. Based on this main task, the church must be able to demonstrate and impart the life of Diakonia, Koinonia and Marturia with the aim of impacting and changing human life. This is what the Ressud Sudirman Surabaya Indonesian Christian Church is aware of in the context of its duties and vocation as a church that has been present in the midst of the Surabaya community, of course its presence is required to fulfill God's plan to become salt and light, a blessing for the surrounding community in general and the congregation in particular. through Diakonia, Koinonia and Marturia's ministry. This research uses a descriptive method. The author directly conducts research, both literature and field research. Bibliography that contains various theoretical data related to topic material from various sources of information which contains important statements to support the accuracy of the research. In addition, this research is also complemented by field research either through questionnaires or direct interviews with several trusted sources including congregants, church activists, servants, sympathizers so that the results of the research present a strong and accurate combination because they are supported by strong theoretical aspects but are also followed by field research evidence. The purpose of this study: first to realize how important the services of Diakonia, Koinonia and Marturia are for the growth of the Indonesian Christian Church in Ressud Surabaya in particular and to the Lord's church in general. Second, the Church is aware of her duty and calling on this earth which has been mandated by God to be her witness so that the impact is evident in church growth both in quality and quantity. Third, the Church of God has the correct concept of the impact of the ministry of Diakonia, Koinonia and Marturia on church growth from the perspective of Missiology, Theology and Ecclesiology. Based on the research conducted by the author, the results obtained are how the extraordinary impact of the services of Diakonia, Koinonia and Marturia on the growth of the Indonesian Christian Church Ressud Surabaya. This is evidenced by the increasing number of church members from year to year and the increasing quality of the congregation's faith. By having a correct understanding of the ministry of Diakonia, Koinonia and Marturia, the congregation will be more active and diligent in carrying out the duties and responsibilities that have been mandated by God to become a blessing, to become salt and light in this world, in various forms of diaconial services such as selling rice. cheap for the congregation and partly distributed by the surrounding community, cheap medical treatment and even free for the congregation and the poor by establishing a polyclinic